2002
DOI: 10.1046/j.1440-1819.2002.00926.x
|View full text |Cite
|
Sign up to set email alerts
|

Hoarding in obsessive–compulsive disorder and related disorders: A preliminary report of 15 cases

Abstract: Hoarding, the repetitive collection of excessive quantities of poorly useable items of little or no value with failure to discard these items over time, is characterized in DSM-IV as a symptom of obsessive-compulsive disorder (OCD) and obsessive-compulsive personality disorder (OCPD) but has, until recently, received scant empirical investigation. We describe the demographics, phenomenology, associated psychopathology and family history in 15 subjects presenting with hoarding behavior. Fifteen subjects were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
46
0
4

Year Published

2007
2007
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(54 citation statements)
references
References 30 publications
4
46
0
4
Order By: Relevance
“…In the present sample, all of our hoarding patients met DSM-IV-TR criteria for at least one comorbid Axis I disorder; depression and anxiety disorders were particularly common. Axis II comorbidity has also been reported in the majority of hoarding cases in other samples (Seedat & Stein, 2002). Thus, many hoarding patients may require additional pharmacological and cognitive-behavioral treatment strategies aimed at reducing comorbid symptoms, particularly when they exacerbate hoarding or interfere with its treatment (e.g., a depressed patient who is too fatigued to comply with homework assignments, a socially phobic patient who is too fearful to allow others into his/ her home, contamination fears that affect ability to touch and sort possessions).…”
Section: Discussionmentioning
confidence: 82%
“…In the present sample, all of our hoarding patients met DSM-IV-TR criteria for at least one comorbid Axis I disorder; depression and anxiety disorders were particularly common. Axis II comorbidity has also been reported in the majority of hoarding cases in other samples (Seedat & Stein, 2002). Thus, many hoarding patients may require additional pharmacological and cognitive-behavioral treatment strategies aimed at reducing comorbid symptoms, particularly when they exacerbate hoarding or interfere with its treatment (e.g., a depressed patient who is too fatigued to comply with homework assignments, a socially phobic patient who is too fearful to allow others into his/ her home, contamination fears that affect ability to touch and sort possessions).…”
Section: Discussionmentioning
confidence: 82%
“…However, there is evidence that hoarding problems may start several decades before these individuals present themselves to clinics or research studies. Although the natural history of compulsive hoarding remains to be investigated systematically in prospective studies, several retrospective studies suggest that hoarding symptoms first emerge in childhood or early adolescence, at an average age of 12-13 (e.g., [19,39,52,97,98] ) and start interfering with individuals' everyday functioning by the mid-30s. [22,52,99] Grisham et al [52] reported that among the different symptoms of hoarding, acquisition had a somewhat later onset than either difficulty discarding or clutter, possibly due to greater financial and physical independence and the means to store a greater volume of possessions.…”
Section: If Hoarding Were To Be Included As a Separate Diagnosis Arementioning
confidence: 99%
“…Presently, parsimony is reflected in DSM-V criterion 5 (is unable to discard worn-out or worthless objects even when they have no sentimental value) and criterion 7 (adopts a miserly spending style towards both self and others; money is viewed as something to be hoarded for future catastrophes) (American Psychiatric Association 2000, 2013). Though so rigidly specified (Hertler 2013) as to become diagnostically inefficient (Mataix-Cols et al 2010;Fossati et al 2006;Seedat and Stein 2002), criteria 5 and 7 are representative of parsimoniousness, the broad temperamental disposition that induces a range of specific behavioral expressions, all of which center on conserving, collecting, and husbanding resources (Hertler 2013). Squirrels, because they inhabit so many continents and contain certain species with broad ranges, serve as particularly good animal models from which to draw lessons about the adaptive value of parsimoniousness.…”
Section: Conservation: Collecting Rationing and Hoardingmentioning
confidence: 99%